Pululahua dome complex, Ecuador: eruptive history, total magma output and potential hazards. (March 2021) - Andrade, S. Daniel; Müller, Anais Vásconez; Vasconez, Francisco J.; Beate, Bernardo; Aguilar, Jorge; Santamaría, Santiago
Abstract: Pululahua is a potentially active dome complex located 15 km north of Quito. It is composed of sixteen dacitic-andesitic lava domes located inside and around a semi-rectangular depression. We divide its eruptive history into: (1) a first member characterized by effusive lava dome growth and collapse (Units I and II, >18–12 ka), (2) a second member consisting of at least four explosive eruptive phases (VEI ~4), responsible for the formation of a caldera-like depression (Unit III, 2.6–2.3 ka cal BP), and (3) a final member encompassing partially explosive dome growth inside the depression (Unit IV, 2.2 ka cal BP). Rock samples show no significant geochemical changes over time, except for a slight decrease in SiO2 and a minor increase in MgO and Fe2 O3 towards younger magmas. In addition, based on field measurements, a total minimum bulk volume of all domes and pyroclastic deposits is estimated at ~5.75 ± 0.14 km³, yielding a dense rock equivalent of ~4.24 ± 0.1 km³ and a total erupted magma mass of 10.58 ± 0.16 E+12 kg. Finally, we put forward three future hazard scenarios that could affect the population in the proximal area (>70 k people): (1) an unrest period involving increased seismic events, volcanic gas emissions and potentially small phreatic explosions, (2) the effusive and/or slightly explosive growth and destruction of lava domes accompanied by block-and-ash flows and tephra fall, and (3) large explosive events (VEI ~ 4) that generate regional tephra fall and massive pyroclastic density currents. Highlights: Pululahua volcano has shown effusive and explosive (VEI 4) activity in the Holocene. Explosive activity extended over 300 years with short repose periods of tens of years. There is no significant change in the chemistry of the Pululahua lavas over time. The minimum total erupted volume is of ~5.75 ± 0.14 km³ (DRE: ~4.24 ± 0.1 km³). Unrest periods, dome growth and Plinian eruptions are possible future hazard scenarios.